Boromycin Kills Mycobacterial Persisters without Detectable Resistance - Moreira, Wilfried; Aziz, Dinah B.; Dick, Thomas (Frontiers in Microbiology, 2016)
Boromycin is a boron-containing polyether macrolide antibiotic isolated from Streptomyces antibioticus. It was shown to be active against Gram positive bacteria and to act as an ionophore for potassium ions. The antibiotic is ineffective against Gram negative bacteria where the outer membrane appears to block access of the molecule to the cytoplasmic membrane. Here we asked whether boromycin is active against Mycobacterium tuberculosis which, similar to Gram negative bacteria, possesses an outer membrane. The results show that boromycin is a potent inhibitor of mycobacterial growth (MIC50 = 80 nM) with strong bactericidal activity against growing and non-growing drug tolerant persister bacilli. Exposure to boromycin resulted in a rapid loss of membrane potential, reduction of the intracellular ATP level and leakage of cytoplasmic protein. Consistent with boromycin acting as a potassium ionophore, addition of KCl to the medium blocked its antimycobacterial activity. In contrast to the potent antimycobacterial activities of the polyether macrolide, its cytotoxicity and haemolytic activity were low (CC50 = 30 µM, HC50 = 40 µM) with a selectivity index of more than 300. Spontaneous resistant mutants could not be isolated suggesting a mutation frequency of less than 10-9 / CFU. Taken together, the results suggests that targeting mycobacterial transmembrane ion gradients may be an attractive chemotherapeutic intervention level to kill otherwise drug tolerant persister bacilli, and to slow down the development of genetic antibiotic resistance.